2020
DOI: 10.1021/acs.macromol.9b02389
|View full text |Cite
|
Sign up to set email alerts
|

Control of Chain Alignment and Crystallization Helps Enhance Charge Conductivities and Thermoelectric Power Factors in Sequentially Doped P3HT:F4TCNQ Films

Abstract: Thermoelectricity has gained considerable interest in the last decade due to the advent of organic thermoelectric materials. Crystallinity and doping level crucially determine the thermoelectric figure of merit of semi-conducting polymers. Hence, detailed insight into these factors is prerequisite for developing efficient devices. Here we show that the semicrystalline structure of aligned P3HT films shows superior thermoelectric efficiencies as compared to the smectic-like phase because of both a higher in-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(175 citation statements)
references
References 53 publications
14
159
2
Order By: Relevance
“…In the case of P3HT, this absence has been attributed to the fact that the amorphous phase of P3HT is little doped with F 4 TCNQ due to a larger offset between the amorphous polymer's HOMO and the dopant's LUMO as compared to crystalline P3HT. [26] The present results with F 6 TCNNQ suggest a similar effect for C 12 -PBTTT: F 6 TCNNQ cannot dope efficiently the amorphous phase of C 12 -PBTTT.…”
Section: Spectroscopysupporting
confidence: 60%
See 3 more Smart Citations
“…In the case of P3HT, this absence has been attributed to the fact that the amorphous phase of P3HT is little doped with F 4 TCNQ due to a larger offset between the amorphous polymer's HOMO and the dopant's LUMO as compared to crystalline P3HT. [26] The present results with F 6 TCNNQ suggest a similar effect for C 12 -PBTTT: F 6 TCNNQ cannot dope efficiently the amorphous phase of C 12 -PBTTT.…”
Section: Spectroscopysupporting
confidence: 60%
“…The same observation was also obtained for the angular distribution measurements of F 4 TCNQ-doped P3HT films. [15,26] In addition to this, the maximum of the angular distributions of both F 4 TCNQand F 6 TCNNQanions are clearly centered at 90. This implies that the long axis of the dopants is indeed oriented around a plane orthogonal to the average polymer chain direction and not tilted.…”
Section: Angular Distribution Of Dopant Anions and Polaronsmentioning
confidence: 77%
See 2 more Smart Citations
“…They can form spontaneously nanostructured bulk heterojunctions via phase separation of donor and acceptor blocks. [77][78][79][80] Preliminary studies show that the alignment methods used for the individual blocks are relevant to orient and crystallize such conjugated copolymers and ultimately study their organization by electron diffraction. In particular, TEM studies demonstrated that the crystallization of the P(NDI2ODT2) block can hamper substantially that of the P3HT block due to a mismatch of lattice parameters of the two blocks at the block junction.…”
Section: Discussionmentioning
confidence: 99%